The Impact of Global Economic Shift on Outward Foreign Investment - Diin Fitri Ande; Rolan Mauludy Dahlan; Samudra Sukardi (BPJP - STEI, 2018)
This paper aims to see the impact of the global economic shift on the pattern of outward foreign direct investment. It was conducted by the literature study method, by comparing a number of countries over different time periods. The results of the study show that the pattern of outward foreign direct investment is strongly influenced by the level of global integration pressure and local pressure responsiveness level. The results fit with Bartlett & Ghoshal's model of international business. It also shows that the pressure of global integration and local responsiveness tend to increase over time. There are 3 factors that need to be considered in this condition, namely: customization, competence and arbitrage. However, these results are obtained from very few case studies. In the future this study needs to be elaborated further by using more samples.